Feature-based characterisation of evolving surface topographies in finishing operations for additive manufacturing - Newton, Lewis; Senin, Nicola; Smith, Bethan; Leach, Richard (2018)
Finishing operations play a fundamental role in the additive manufacture of components. Conventional surface metrology solutions allow for the characterisation of surface roughness through texture parameters, but are not fully suitable to capture the evolution of individual surface topographic formations as they undergo changes as a result of finishing operations. Feature-based characterisation of topography offers a new perspective in the investigation of surfaces. The approach consists of the identification, isolation, and dimensional characterisation of surface topography formations (surface features). In this work an original feature- based solution is proposed for the quantitative comparison of topographies before and after a finishing operation: the approach is based on the registration of areal topography datasets and quantitative analysis of shape and size differences pertaining to the relevant topographic features. A variety of finishing operations are investigated on metallic samples manufactured via powder bed fusion.